Сердце дезертира: фантастический роман / А. Степанов - Степанов Алексей (STALKER, 2010)
Экземпляры: аб. ЦБ (2017.14.12) / Инвентарный номер: 3671 / Цена: / Сис.шифр: 84 (2 Рос=Рус)6 / Авт.знак: С 79 / ГРНТИ: 17 / ББК: 84 (2 Рос=Рус)6